2021
DOI: 10.1521/pedi_2019_33_454
|View full text |Cite
|
Sign up to set email alerts
|

Mentalization-Based Treatment Versus Specialist Treatment as Usual for Borderline Personality Disorder: Economic Evaluation Alongside a Randomized Controlled Trial With 36-Month Follow-Up

Abstract: Patrick Luyten has been involved in the training and dissemination of mentalization-based treatments. The other authors declare that they have no competing interests. We would like to thank Laura Bakker, Carolien Christ, and Isabel Alvarez Perez for their hard work in collecting the data. We are also very grateful to all the patients who participated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…27 Seven studies only recruited participants with a diagnosis of borderline personality disorder. 16, 18,19,23,26,29,31 Nine of the studies required a recent episode of self-harm, attendance at an emergency department or in-patient stay. 15,1721,23,29 Two studies only included patients with other comorbid severe mental illness 24 and one of the two also required substance dependence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Seven studies only recruited participants with a diagnosis of borderline personality disorder. 16, 18,19,23,26,29,31 Nine of the studies required a recent episode of self-harm, attendance at an emergency department or in-patient stay. 15,1721,23,29 Two studies only included patients with other comorbid severe mental illness 24 and one of the two also required substance dependence.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were identified which looked at other interventions: joint crisis plans, 29 psychoeducation with problem-solving, 30 clarification-oriented psychotherapy (COP) 14 and mentalisation-based treatment delivered in a day hospital (MBT). 31 All of them used RCT data and employed a CUA, and two of these studies (Blankers et al 31 and Bamelis et al 14 ) also conducted a CEA. All of these studies took a broad perspective.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the evaluations looked at ‘Cluster C personality disorders’, described as avoidant, dependent, obsessive-compulsive (Bamelis et al 2015a, Bamelis et al 2015b, Soeteman et al 2011) (14,20) and one study looked at ‘Cluster B personality disorders’ described as antisocial, borderline, histrionic, and narcissistic (Soeteman et al 2010) (21). Eight studies only recruited participants with a ‘borderline personality disorder’ diagnosis (Blankers et al 2019, Borschmann et al 2013, Davidson et al 2010, Palmer et al 2006, Pasieczny & Connor 2011, Sinnaeve et al 2018, van Asselt et al 2008) (2228). Nine of the studies required a recent episode of self-harm, attendance at an emergency department, or in-patient stay (Borschmann et al 2013, Davidson et al 2010, Grenyer et al 2018, Murphy et al 2019, Palmer et al 2006, Pasieczny & Connor 2011, Priebe et al 2012, Sinnaeve et al 2018, Tyrer et al 2004) (15,18,2327,29,30).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were identified which looked at other interventions: joint crisis plans (JCPs) (23), psycho-education with problem solving (PEPS) (16), clarification orientated psychotherapy (COP) (14) and mentalization-based treatment delivered in a day hospital (MBT) (22). All of them used randomised controlled trial data and employed a CUA, and two of these studies, Blankers et al and Bamelis et al (2015b), also conducted a CEA (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…A study by van Asselt et al (2009) showed that it is quite responsive for treatment improvement in borderline personality disorder (BPD). However, several studies also report remarkable discrepancies between clinical improvement in BPD patients and improvement in EQ-5D scores (Blankers et al, 2019;van Asselt et al, 2008). When quality of life was studied in a broader approach by Cramer et al (2007), the presence of a PD appeared to be the strongest negative predictor of quality of life.…”
Section: Discussionmentioning
confidence: 99%